The Assumption of the Judiciary in Palestinian Territories: Balancing Islamic Law and Secular Law - Alorgan, Gaber Mohammed (Journal of Economic, Administrative and Legal Sciences, 2024)
This paper shows the Islamic provision of the assumption of judges in Sharia courts within the Palestinian territories. Besides, it explains the various types of Sharia courts, their historical legitimacy, their hierarchy, and their jurisdiction. It also discusses the provision of resorting Muslims in the Palestinian territories to civil courts, which have equivalent authority to Sharia courts, despite the presence of Sharia courts within the Palestinian territories.
Keywords: Palestinian Territories; Sharia Judiciary; Sharia Court